Efektifitas Blended Learning Berbasis Guided Discovery Learning Untuk Meningkatkan Kemampuan Berpikir Kritis - Nasution, Siti Suaibah; Fauzi, KMS.Muhammad Amin; Mulyono, Mulyono (UIR Press, 2025)
The objectives of this study are 1) to analyze the significant difference between students' initial and final abilities, 2) to evaluate the level of students' mathematical critical thinking skills, and 3) to analyze the effectiveness of the model after the implementation of blended learning based on Guided Discovery Learning. This type of research is a pre-experiment with one group pretest-postes. The sample consisted of 35 students of Sharia Banking in the first semester of 2024/2025 at the State Islamic University of North Sumatra. This study showed that 1) significant differences in students' initial and final abilities, 2) an increase in students' mathematical critical thinking skills worth 0.83 with a high category, and 3) the effectiveness of Blended Learning based on Guided Discovery Learning to improve students' mathematical critical thinking skills worth 82.84%. The variety of answers given by technology-based students requires advanced analysis to determine the relationship between critical and creative thinking skills in Blended Learning based on Guided Discovery Learning, analyzing the influence of Canva on Blended Learning based on Guided Discovery Learning and conduct research on the development of students’ worksheets based on Guided Discovery Learning assisted by Canva.